GERAKAN INTELEKTUAL KAJIAN JARINGAN ISLAM LIBERAL - Zainol Hasan (LP2M Universitas Ibrahimy, 2016)
The term Liberal Islam Network was not well known and was not noticed by people in Indonesia. Moreover, the number of proponents’ is very small, can be counted on the fingers. It presents a new face of Islam which is in the form of non-orthodox, Islam that has compatibility with alteration of era and Islam that has an insight into the future. That is not Islam that has ignorance into the future or that is not outdated. But the ideas promoted by them get a strong reaction from the public, either from the Indonesian religious leaders, or from the Indonesian Moslem intellectuals. Therefore, the term Liberal Islam Network was actually popularized by the opponents.